(untitled) (Bangladesh Journal of Botany, 2021)
Effects of cropping pattern on soil carbon sequestration and their aggregate stability in long term agricultural fields was investigated in 2018. Four cropping patterns were selected that have been cultivated for last ten years. Results showed that Soil organic carbon (SOC) value was improved for vegetable field from 4.06 to 9.11 g/kg and carbon stock (20.14 Mg C ha/yr) as well as soil carbon sequestration rate was the highest in vegetable field (1.12 Mg C ha/yr). The logarithmic relationship between the C input and C sequestration rate showed the strong correlation (r = 0.72, p < 0.05). In terms of aggregate stability, vegetable field put the best result (0.41 mm) (p > 0.05). The straight-line relation between aggregate stability and Cstock established that they are strongly correlated (r = 0.81, p < 0.05). Finally, results indicated that Vegetable-Vegetable-Vegetable cropping pattern was the best soil carbon sequester along with the best aggregate stability. Bangladesh J. Bot. 50(4): 1029-1034, 2021 (December)